The Study of the Linear Morphometry of Suktel River Basin, Odhisha - Patel, Ramesh Kumar (National Geographical Journal of India, 2022)
In the present study, an attempt is made to study the linear morphometry of Suktel River, a tributary of Tel River and its subbasins that ows through Bolangir District of Odisha. Freely available SRTM Dem (30- meter resolution) has been processed to delineate the streams and the watershed. It's various linear, parameters have been delineated using Arc GIS 10.3. The results show that Suktel basin is a sixth-order normal basin having a dendritic drainage pattern. It conrms to Horton's Law of stream number and lacks structural control as implied by its bifurcation ratio that ranges between 3 and 5. It is in the stage of late maturity with the high volume of surface discharge.